Comparison of 2% Mepivacaine, Clipping, and Radiofrequency Thermocoagulation for Duration and Magnitude of Action in Peripheral Arterial Blood Flow Induced by Sympathetic Block in Anesthetized Dogs. Issue 6 (1st October 2010) - Otani, Taro; Shinozaki, Mio; Takahashi, Yoshiyuki; Ikeda, Tomohito; Kimura, Yoshiyuki; Nagao, Masaru; Yamaguchi, Shigeki; Kitajima, Toshimitsu
Abstract : Background and Objectives: Thoracic sympathetic block has recently been performed by placement of the clips on the sympathetic chain to interrupt nerve conduction. The aim of this study was to compare clipping with 2% mepivacaine and radiofrequency thermocoagulation for the potency of sympathetic block from the results of the duration and magnitude of the vasodilation effect induced by thoracic sympathetic block in dogs. Methods adiofrequency: We measured mean arterial pressure, heart rate, and right and left brachial artery blood flow (BABF) before and after thoracic sympathetic block in 24 dogs. The experimental protocol was designed as follows: (1) left thoracic sympathetic block by 1.0 mL of 2% mepivacaine (n = 8), (2) left thoracic sympathetic block by clipping (n = 8), and (3) left thoracic sympathetic block by radiofrequency thermocoagulation (n = 8). Results: Mean arterial pressure and heart rate did not change significantly throughout the study in either group. Left thoracic sympathetic block by 2% mepivacaine increased left BABF significantly from 5 to 70 mins after the block (baseline, 100%; peak at 10 mins after the block, 179% ± 33%; P < 0.01). Left thoracic sympathetic block by clipping increased left BABF significantly from 5 to 120 mins after the block (baseline, 100%; peak at 30 mins after the block, 156% ± 31%; P < 0.01). Left thoracic sympathetic block by radiofrequency thermocoagulation increased left BABF significantly from 5 to 120 mins after the block (baseline, 100%; peak at 10 mins after the block, 206% ± 31%; P < 0.01). Conclusions: Clipping may have a same potency compared with 2% mepivacaine and a less potency compared with radiofrequency thermocoagulation in thoracic sympathetic block in dogs.